Security Management Technology of Multilayer Satellite Internet Based on Blockchain - Ruijie ZHU; Yudong ZHANG; Yating WEI; Chao XI (天地一体化信息网络)
Satellite internet have the advantages of wide coverage, low latency, large transmission capacity and no geographical infl uence.It can provide ubiquitous internet access services for users all over the world.However, the heterogeneity of satellite internet and ground network, the channel opening and node exposure of satellite internet will pose a security threat to network access and resource management.Aiming at the security problem of satellite internet, a multilayer satellite internet security management architecture based on blockchain was proposed.As a distributed ledger technology, blockchain uses chain data structure to verify and store data, and adopts encryption methods to maintain that data blocks cannot be tampered.Blockchain can realize network security access, trusted resource management, and provide information security protection for satellite internet.This paper improved the security of satellite internet by integrating blockchain technology with satellite internet.